Time Variation in Lifecycle Consumption and Income - Yunus Aksoy; Henrique S. Basso; Carolyn St. Aubyn (Center for Economic Studies and ifo Institute (CESifo), 2020)
We document systematic and significant time variation in US lifecycle non-durable consumption profiles. Consumption profiles have consistently become flatter: differences in consumption across generations have decreased. Pooling data across different periods to identify lifecycle profiles masks relevant time variations and may artificially generate hump-shaped consumption age profiles. The main driver behind lifecycle consumption variations are lifecycle income changes, which display similar flattening. Employing a lifecycle model we show changes in income are sufficient to match the movements in consumption. The contributions of credit, housing and interest rates changes are quantitatively small.
Keywords: E21; J11; 330; age profile of consumption; age profile of income; consumption heterogeneity; time variation; pooling